(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Proteus mirabilishas the ability to infiltrate and colonize woundscausing wound infections in both community and hospitalized patients. Due to the production of extended-spectrum-lactamases, P. mirabilis has developed resistance to beta-lactam antibioticsas a result of conventional use of antibioticslimitingtreatment options for clinicians.The current study is aimed to determine the phylogenic analysis and molecular characterization of antibiotic resistant genes of P. mirabilisrecovered from infected patients of skin and soft tissue wounds.A total of 800wound samples were obtained from infected wound patientsat Khyber Teaching Hospital (KTH) and Hayatabad Medical Complex (HMC),Peshawar.The collected samples were identified phenotypically using API 20E strips and antibiogram was determined using standard procedures. Molecular identification was done through sequencing of 16sRNA and phylogenetic analysis was performed using Molecular Evolutionary Genetics Analysis (MEGA-7) software. The antibiotic resistant genes of P. mirabilis were detected by PCR using specific primers.Out of 800 samples,84 isolatesyielded the growth ofP. mirabilis.Phylogenetic tree revealed that 100% of samples No. A-1 and No. A-2 are closely related to P. mirabilis to NR 043997.1:1-1503 P. mirabilis strain NCTC 11938 and 99%to (NR 114419.1:1-1495 P. mirabilis strain ATCC 29906).The results of antibiogram revealed that most of the isolates were resistant against antibiotics; cephalosporins, ampicillin, quinolones, chloramphenicol and aminoglycosides while showed good results against MEM, TZP and SCF.Of the isolates, 72.6% were found positive for ESBLs production. Molecular analysis showed that 40%of isolates were positive for blaTEM, blaCTX-M 14 (20%) and blaCTX-M (5%).The current study showed that the prevalence of blaTEM, blaCTX-M and blaCTX-M-14 genes carrying P. mirabilis in a tertiary care hospital Peshawar Pakistan. Phylogenetic analysis shows that sequences are closely related with the reference sequences ofP. Mirabilisamong infected patients of skin and soft tissue woundsand is resistant to the commercially available antibioticsresulting in a therapeutic challenge for clinicians.